Hollow silica sol, its preparation method, coating composition and product
By controlling the surface chemistry and structure of hollow silica sols through specific Si NMR peak ratios and hydrothermal treatment, the issues of hardness, stability, and abrasion resistance are addressed, resulting in improved antireflection coatings with enhanced mechanical properties.
Patent Information
- Application Number
- JP2024518354
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-04-23
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2043-04-23
AI Technical Summary
Existing hollow silica particles used in antireflection coatings suffer from poor hardness, high reflectance, low moisture and heat resistance, and poor abrasion resistance due to surface defects and hydroxyl groups, leading to instability and high viscosity.
A method to prepare hollow silica sols with controlled surface chemistry and structure, involving specific ratios of Si nuclear magnetic resonance peaks and hydrothermal treatment to create a dense shell layer, reducing hydroxyl groups and enhancing mechanical properties.
The resulting hollow silica sols exhibit low viscosity, improved stability, high hardness, and excellent abrasion resistance, with enhanced antireflection properties and improved heat and humidity resistance when used in coating layers.
Smart Images

Figure 0007619707000004 
Figure 0007619707000005 
Figure 0007619707000006
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to Chinese Patent Application No. 202210773132.2, filed on July 1, 2022, entitled "Hollow Silica Sol, Its Preparation Method, Coating Composition and Product," which is incorporated herein by reference in its entirety.
[0002] The present application relates to hollow silica sols, their preparation methods, coating compositions and products. [Background technology]
[0003] Hollow silica particles have characteristics such as high porosity, low refractive index, low dielectric constant, and non-toxicity to living organisms, and therefore are widely used in fields such as weight reduction, low refractive index materials, anti-reflective coatings, semiconductor materials, and the carrying and sustained release of active molecules.
[0004] In the application fields such as low refractive index materials and anti-reflection films, hollow silica particles are generally required to have a size between several tens and several hundreds of nanometers, and if the particle size is too large, the optical transparency is reduced and it is not practical.In addition to the size of the particles themselves, they are required to have good dispersion stability without causing aggregation during use, and a gel with stable dispersion can facilitate subsequent use and avoid the dispersion difficulties associated with the use of powder particles.
[0005] In CN110128855A, the present inventor has disclosed a method for preparing hollow silica particles, which uses hydrolysis and condensation of silane monomers in water to prepare amphiphilic polyalkoxysiloxanes, and uses the self-organization behavior of the amphiphilic polyalkoxysiloxanes in an aqueous medium to prepare hollow silica particles. The hollow silica particles have excellent dispersibility and size controllability, and are suitable for use in the field of antireflection. However, when the hollow particles are used to prepare an antireflection film, there are problems such as low hardness of the coating layer, poor total light transmittance, high reflectance, poor resistance to moist heat, insufficient adhesion, and poor abrasion resistance. In addition, the sol prepared using the hollow silica particles has high viscosity, poor stability, and cannot withstand storage. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] CN110128855A Summary of the Invention [Problem to be solved by the invention]
[0007] In view of the problems existing in the above-mentioned prior art, the present inventors have conducted intensive research and found that the surface defects of hollow silica particles contained in hollow silica sol reduce the hardness of the coating layer obtained by using said particles, and the abrasion resistance is poor.In addition, the cause of surface defects is that the internal cavities of hollow particles are easily filled with adhesives, solvents, etc., and the refractive index reduction when used as an anti-reflection film is not noticeable, the anti-reflection properties are poor, and the moist heat resistance is also poor.In addition, the existence of surface defects indicates that the particle surface is rich in hydroxyl groups, and when stored as a sol, there are problems such as instability, high viscosity, and easy gelation. [Means for solving the problem]
[0008] The present invention has been made to solve at least part of the above-mentioned problems, and aims to provide a hollow silica sol that has low viscosity, excellent stability, and when a coating layer is formed on a substrate, has high hardness, excellent abrasion resistance, and improves adhesion to the substrate. In addition, when a transparent coating layer is formed as an antireflection layer, the refractive index is low, antireflection properties are improved, and moist heat resistance is improved.
[0009] The present invention also aims to provide a method for preparing hollow silica sol, and the hollow silica sol prepared by this method has low viscosity and improved stability, and when a coating layer is formed on a substrate, the hardness and abrasion resistance are improved, and the adhesion to the substrate is improved. Also, when a transparent anti-reflection layer is formed, the refractive index is reduced, the anti-reflection property is improved, and the moist heat resistance is improved.
[0010] A further object of the present invention is to provide a coating composition containing the hollow silica sol of the present invention or the hollow silica sol prepared by the above-mentioned method for preparing a hollow silica sol of the present invention, and an adhesive.
[0011] Another object of the present invention is to provide a product having a coating layer formed by curing the coating composition of the present invention on the surface of a substrate. This coating layer has high hardness, excellent abrasion resistance, and improved adhesion to the substrate. In addition, when a transparent coating layer is formed as an anti-reflection layer, it has a low refractive index, improved anti-reflection properties, and improved moist heat resistance.
[0012] The present invention provides the following embodiments.
[0013] [1] A dispersion medium containing hollow silica particles, The hollow silica particles are 29 A resonant peak area Q1 having a chemical shift of -78 to -88 ppm, a resonant peak area Q2 having a chemical shift of -88 to -98 ppm, a resonant peak area Q3 having a chemical shift of -98 to -108 ppm, and a resonant peak area Q4 having a chemical shift of -108 to -117 ppm corresponding to peaks measured by Si nuclear magnetic resonance spectroscopy satisfy the following conditions: Q1 / (Q1+Q2+Q3+Q4) is essentially 0, Q2 / (Q1+Q2+Q3+Q4) is 0.01 to 0.2, Q3 / (Q1+Q2+Q3+Q4) is 0.01 to 0.6, and Q4 / (Q1+Q2+Q3+Q4) is 0.2 to 0.98, The hollow silica sol, wherein the dispersion medium is water, an organic solvent or a combination of both.
[0014] [2] The hollow silica sol according to [1], wherein the hollow silica particles have a shell layer having a thickness of 3 to 100 nm, and the pore size distribution of the pores on the shell layer is in the range of 0.5 to 4 nanometers.
[0015] [3] The hollow silica particles have a pore volume of 0.15 to 1 cm. 3 / g, a porosity of 10% to 90%, and a refractive index of 1.10 to 1.45.
[0016] [4] The hollow silica sol according to any one of [1] to [3], wherein the hollow silica particles have a relative dielectric constant of 1.6 to 2.2.
[0017] [5] The hollow silica sol according to any one of [1] to [4], wherein the hollow silica particles have a particle diameter of 15 to 1000 nm as measured by a dynamic light scattering method and a polydispersity index of 0.05 to 0.3.
[0018] [6] An intermediate product production step of mixing a silicon source, a first solvent, a first catalyst and an active compound, reacting them at a temperature in the range of 0 to 150°C, and removing those having a boiling point of less than 300°C to obtain a liquid silicone intermediate product P1; a hollow silica production step of dispersing the silicone intermediate product P1 in a second solvent, adding a second catalyst, and reacting at a temperature in the range of 0 to 95° C. to obtain a hollow silica sol; A hydrothermal treatment process in which hydrothermal treatment is performed within a range of 30 to 300°C. The method for preparing a hollow silica sol according to any one of [1] to [5], comprising:
[0019] [7] In the intermediate product formation step, the silicon source is one or more selected from silane monomers represented by the following formula I, or is a polyalkoxysiloxane oligomer having an empirical formula represented by the following formula II, the method for preparing a hollow silica sol according to [6]. R 1 4-n Si(OR 2 ) n Formula I (In the formula, n is 1, 2, 3 or 4, R 1 is an alkyl group, a vinylalkyl group, a vinyl group, an epoxyalkyl group, a phenyl group, a styrylalkyl group, a methacryloxyalkyl group, an acryloxyalkyl group, an aminoalkyl group, a urethane group, a chloroalkyl group, a mercaptoalkyl group, an isocyanatoalkyl group or a hydroxyalkyl group, and when there are a plurality of R 1 , each R 1 may be the same as or different from each other, R 2 is an alkyl group having 1 to 6 carbon atoms, and when there are a plurality of R 2 , each R 2 may be the same as or different from each other.) SiO m (OR 3 ) 4-2m Formula II (In the formula, 0 < m < 2, m is an integer or a non-integer, R 3 is an alkyl group having 1 to 6 carbon atoms, and when there are a plurality of R 3 , each R 3 may be the same as or different from each other.)
[0020] [8] In the intermediate product formation step, the first solvent is water or an organic solvent containing water, and the weight ratio of water to the silicon source is 0.001:1 or more and less than 0.5:1, the method for preparing a hollow silica sol according to [6] or [7].
[0021] [9] The method for preparing a hollow silica sol according to any one of [6] to [8], wherein in the intermediate product generation step, the first catalyst is an acid or a base, and a weight ratio of the first catalyst to the silicon source is (0.001 to 0.5:1).
[0022]
[10] In the intermediate product production step, the active compound contains at least one OH group, has a molecular weight of more than 150, and has an HLB value of the active compound calculated by the following formula III of more than 5; HLB=20×M h / M formula III (In the formula, M h is the molecular weight of the hydrophilic portion of the active compound, and M is the molecular weight of the active compound. The method for preparing a hollow silica sol according to any one of [6] to [9], wherein the weight ratio of the active compound to the silicon source is (0.05 to 0.5):1, and the active compound is one type or a mixture of two or more types.
[0023]
[11] In the hollow silica generating step, the second solvent is water, a mixture of water and a hydrophilic organic solvent, or a mixture of water and a hydrophobic organic solvent; the second catalyst is an acid or a base; the weight percentage of the silicone intermediate product P1 relative to the second solvent is 1 to 60%; The method for preparing a hollow silica sol according to any one of [6] to
[10] , wherein a weight ratio of the second catalyst to the silicone intermediate product P1 is (0.05 to 2:1).
[0024]
[12] The method further comprises a solvent replacement step of replacing the solvent of the hollow silica sol, The method for preparing a hollow silica sol according to any one of [6] to
[11] , wherein in the solvent substitution step, all or a part of the solvent in the hollow silica sol is substituted by centrifugation, heating azeotropy or ultrafiltration treatment.
[0025]
[13] The method further comprises a surface modification step of adding one or more members selected from the group consisting of a silane represented by the following formula IV and / or a partial hydrolyzate thereof, hexamethyldisiloxane, and hexamethyldisilazane to the hollow silica sol to modify the surfaces of the hollow silica particles, R 4 p -Si-X 4-p Formula IV (wherein p is 0, 1, 2 or 3; R 4 is selected from an alkyl group, a vinyl alkyl group, an epoxy alkyl group, a styryl alkyl group, a methacryloxy alkyl group, an acryloxy alkyl group, an amino alkyl group, a urethane group, a chloro alkyl group, a mercapto alkyl group, an isocyanato alkyl group, or a hydroxy alkyl group; R 4 If there are multiple R 4 may be the same or different, R 4 may be substituted with fluorine atoms, X is selected from an alkoxy group having 1 to 6 carbon atoms, halogen, or hydrogen, and when there are multiple X's, each X may be the same or different. The method for preparing a hollow silica sol according to any one of [6] to
[11] , wherein the surface modification step is carried out after the hollow silica production step and / or after the hydrothermal treatment step.
[0026]
[14] The method further comprises a surface modification step of adding one or more members selected from the group consisting of a silane represented by the following formula IV and / or a partial hydrolyzate thereof, hexamethyldisiloxane, and hexamethyldisilazane to the hollow silica sol to modify the surfaces of the hollow silica particles, R 4 p -Si-X 4-p Formula IV (wherein p is 0, 1, 2 or 3; R 4is selected from an alkyl group, a vinyl alkyl group, an epoxy alkyl group, a styryl alkyl group, a methacryloxy alkyl group, an acryloxy alkyl group, an amino alkyl group, a urethane group, a chloro alkyl group, a mercapto alkyl group, an isocyanato alkyl group, or a hydroxy alkyl group; R 4 If there are multiple R 4 may be the same or different, R 4 may be substituted with fluorine atoms, X is selected from an alkoxy group having 1 to 6 carbon atoms, halogen, or hydrogen, and when there are multiple X's, each X may be the same or different. The method for preparing a hollow silica sol according to
[12] , wherein the surface modification step is carried out after the hollow silica production step, and / or after the hydrothermal treatment step, and / or after the solvent replacement step.
[0027]
[15] The method for preparing a hollow silica sol according to
[14] , wherein the hydrothermal treatment step and / or the solvent replacement step are carried out again after the surface modification step.
[0028]
[16] A coating composition comprising a hollow silica sol and an adhesive, wherein the hollow silica sol is prepared by the sol described in any one of [1] to [5] or the method for preparing a hollow silica sol described in any one of [6] to
[15] .
[0029]
[17] A product having a coating layer on a surface of a substrate, the coating layer being one or more layers, at least one of the coating layers being formed by curing the coating composition described in
[16] . Effect of the Invention
[0030] According to the hollow silica sol of the present invention, the Q4 (ratio of Si atoms to which four -OSi- groups are bonded), Q3 (ratio of Si atoms to which three -OSi- groups and one hydroxy group are bonded), Q2 (ratio of Si atoms to which two -OSi- groups and two hydroxy groups are bonded), and Q1 (ratio of Si atoms to which one -OSi- group and three hydroxy groups are bonded) of the hollow silica particles contained therein satisfy the conditions that Q1 / (Q1+Q2+Q3+Q4) is substantially 0, Q2 / (Q1+Q2+Q3+Q4) is 0.01 to 0.2, Q3 / (Q1+Q2+Q3+Q4) is 0.01 to 0.6, and Q4 / (Q1+Q2+Q3+Q4) is 0.2 to 0.98, and the shell layer of the hollow silica particles has a small pore size and is thin and dense. Therefore, the hollow silica sol of the present invention has low viscosity, and is excellent in thermal stability and dispersion stability.In addition, the hollow particles in the hollow silica sol of the present invention have a good shell layer structure, and when forming a coating layer, they have high hardness, good abrasion resistance, strong adhesion to the substrate, and can prevent the inside of the cavity from being filled with other substances, so when formed as a coating layer, they have a lower refractive index.In addition, when the coating layer formed is used as an anti-reflection layer, anti-reflection properties and moist heat resistance are improved.
[0031] According to the method for preparing a hollow silica sol of the present invention, the hollow silica sol is subjected to hydrothermal treatment to further condense the hydroxy groups on the surfaces of the hollow silica particles in the hollow silica sol, thereby making it possible to prepare a hollow silica sol having a low viscosity and containing thin and dense hollow silica particles with a small pore size in the shell layer.
[0032] The coating composition of the present invention can form a coating film having obvious anti-reflection effect, excellent abrasion resistance, high hardness, and strong adhesion to the substrate.
[0033] The product according to the present invention has an excellent anti-reflection effect, good hardness, abrasion resistance, adhesion to the substrate, and excellent weather resistance such as moist heat resistance. [Brief description of the drawings]
[0034] [Figure 1] 1 is a transmission electron microscope photograph of the hollow silica particles obtained in Example 1. [Diagram 2] 1 is a transmission electron microscope photograph of the hollow silica particles obtained in Example 2. [Diagram 3] 1 is a transmission electron microscope photograph of the hollow silica particles obtained in Example 3. [Figure 4] 1 is a transmission electron microscope photograph of hollow silica particles obtained in Comparative Example 1. [Diagram 5] 2 is a transmission electron microscope photograph of the hollow silica particles obtained in Comparative Example 2. [Figure 6] 1 is a transmission electron microscope photograph of hollow silica particles obtained in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] [Hollow silica sol] The hollow silica sol according to the present invention contains hollow silica particles and a dispersion medium, Hollow Silica Particles 29 A resonant peak area Q1 having a chemical shift of -78 to -88 ppm, a resonant peak area Q2 having a chemical shift of -88 to -98 ppm, a resonant peak area Q3 having a chemical shift of -98 to -108 ppm, and a resonant peak area Q4 having a chemical shift of -108 to -117 ppm corresponding to peaks measured by Si nuclear magnetic resonance spectroscopy satisfy the following condition. Q1 / (Q1+Q2+Q3+Q4) is essentially 0, Q2 / (Q1+Q2+Q3+Q4) is 0.01 to 0.2, Q3 / (Q1+Q2+Q3+Q4) is 0.01 to 0.6, and Q4 / (Q1+Q2+Q3+Q4) is 0.2~0.98.
[0036] Here, the peak assigned to Q1 is a peak associated with the structure of a silicon atom having one -OSi- group and three hydroxyl groups bonded to a Si atom, the peak assigned to Q2 is a peak associated with the structure of a silicon atom having two -OSi- groups and two hydroxyl groups bonded to a Si atom, the peak assigned to Q3 is a peak associated with the structure of a silicon atom having three -OSi- groups and one hydroxyl group bonded to a Si atom, and the peak assigned to Q4 is a peak associated with the structure of a silicon atom having four -OSi- groups bonded to a Si atom.
[0037] "Q1 / (Q1+Q2+Q3+Q4) is substantially 0" means that the peak associated with the structure of a silicon atom having one -OSi- group and three hydroxyl groups bonded to the Si atom is substantially not contained. However, due to unavoidable peaks caused by detection limits, noise, etc., cases where Q1 / (Q1+Q2+Q3+Q4) is, for example, 0.0001 or less are not excluded, and in this case, Q1 / (Q1+Q2+Q3+Q4) is also considered to be substantially 0.
[0038] Q2 / (Q1+Q2+Q3+Q4) is 0.2 or less. Considering that the hydroxyl groups on the surface of the hollow silica have hydroxyl groups necessary for subsequent solvent replacement and / or surface modification, and that the adhesion after the coating layer is formed is satisfactory, Q2 / (Q1+Q2+Q3+Q4) is preferably 0.01 or more, more preferably 0.03 or more, and even more preferably 0.05 or more.
[0039] Q3 / (Q1+Q2+Q3+Q4) is 0.6 or less. Considering that the hydroxyl groups on the surface of the hollow silica have hydroxyl groups necessary for subsequent solvent replacement and / or surface modification, and that the adhesion after the coating layer is formed is satisfactory, Q3 / (Q1+Q2+Q3+Q4) is preferably 0.01 or more, more preferably 0.1 or more, even more preferably 0.2 or more, more preferably 0.3 or more, and even more preferably 0.4 or more.
[0040] The larger Q4 / (Q1+Q2+Q3+Q4) is, the more complete the shell structure is, the denser the surface is, and the higher the mechanical strength is. Considering that the hollow particles have sufficient mechanical properties, are not easily broken, are not easily filled with internal cavities, and have good antireflection properties when forming coating layers and products, Q4 / (Q1+Q2+Q3+Q4) is 0.2 or more. On the other hand, considering that the surface is not a completely hydrophobic Si-O-Si structure, but has sufficient hydrophilicity to stabilize the hollow silica sol, is not easily precipitated, and can be modified to be easily dispersed in other solvent systems and paint systems, and also considers the adhesion and abrasion resistance of the resulting coating layers and products, Q4 / (Q1+Q2+Q3+Q4) is preferably 0.98 or less, more preferably 0.8 or less, and even more preferably 0.6 or less.
[0041] By adjusting the ratio of Q1, Q2, Q3 and Q4 of the hollow silica particles, the hollow silica sol of the present invention has sufficient hydroxyl groups on the surface of the hollow particles to facilitate dispersion in water and other solvents, forming a stable silica sol and facilitating subsequent surface functionalization, thereby making it applicable to coating compositions of different systems, and also achieving a combination of not having excessive hydroxyl groups on the surface of the hollow particles, a dense surface structure, excellent mechanical properties, a small viscosity of the hollow silica sol and excellent storage stability.
[0042] In particular, the smaller Q2 / (Q1+Q2+Q3+Q4) and Q3 / (Q1+Q2+Q3+Q4) are, the denser the shell of the resulting hollow particles will be and the higher the mechanical strength will be. However, if Q2 / (Q1+Q2+Q3+Q4) and Q3 / (Q1+Q2+Q3+Q4) are too small, the number of hydroxyl groups on the surface of the hollow silica particles will be too small, making it difficult to meet the needs of solvent replacement and / or surface modification required when used in a coating layer later. As a result, the solvent of the sol cannot be replaced with a desired solvent, or a desired amount of functional groups cannot be imparted by surface modification, and furthermore, the adhesion when forming a coating layer later will be insufficient. Therefore, in some embodiments of the hollow silica sol, (Q2+Q3) / (Q1+Q2+Q3+Q4) is preferably 0.2 or more, more preferably 0.45 or more.
[0043] The hollow silica sol according to the present invention has a viscosity at 25°C and a solid content of 20% of, for example, 5 to 200 mPa sec. In consideration of having good storage stability, the viscosity is preferably 5 to 100 mPa sec., more preferably 5 to 50 mPa sec., and even more preferably 5 to 20 mPa sec.
[0044] In some embodiments of the hollow silica sol according to the present invention, Q1, Q2, Q3, and Q4 satisfy the following: Q1 / (Q1+Q2+Q3+Q4) is substantially 0, Q2 / (Q1+Q2+Q3+Q4) is 0.05 to 0.1, Q3 / (Q1+Q2+Q3+Q4) is 0.2 to 0.55, and Q4 / (Q1+Q2+Q3+Q4) is 0.35 to 0.75.
[0045] In some other embodiments of the hollow silica sol according to the present invention, Q1, Q2, Q3, and Q4 satisfy the following: Q1 / (Q1+Q2+Q3+Q4) is substantially 0, Q2 / (Q1+Q2+Q3+Q4) is 0.05 to 0.2, Q3 / (Q1+Q2+Q3+Q4) is 0.35 to 0.6, and Q4 / (Q1+Q2+Q3+Q4) is 0.3 to 0.65.
[0046] The measurement methods for Q1, Q2, Q3, and Q4 are the same as those described in the Examples below, and therefore will not be repeated here.
[0047] The hollow silica particles refer to particles whose shell layer is mainly composed of silica and whose inside is hollow. The term "shell layer mainly composed of silica" means that the main component of the shell layer of the hollow particles is silica, and may optionally contain small amounts of other oxides and / or organic groups.
[0048] In one embodiment of the hollow silica sol according to the present invention, the thickness of the shell layer of the hollow silica particles is preferably, for example, 3 to 100 nm. When the thickness of the shell layer is 3 nm or more, it has sufficient strength, and is more preferably 4 nm or more. The thickness of the shell layer is preferably, for example, 100 nm or less, more preferably 50 nm or less, and even more preferably 10 nm or less, which makes it easier to obtain a suitable refractive index, and is more preferably 6 nm or less. The thickness of the shell layer can be appropriately adjusted depending on the amount of reaction raw materials such as a silicon source used in the preparation conditions of the hollow particles, the reaction temperature, and the like. From the viewpoint of obtaining an excellent refractive index, the thickness of the shell is more preferably 4 to 10 nm.
[0049] The thickness of the shell layer is measured by the following method: observing the hollow particles with a transmission electron microscope (TEM), randomly selecting 100 particles, measuring the shell thickness of each hollow particle, and taking the average of the thicknesses obtained as the shell layer thickness.
[0050] In one embodiment of the hollow silica sol according to the present invention, the shell layer of the hollow silica particles has pores with a diameter distribution of, for example, 0.5 to 4 nanometers. When the pores are 0.5 nanometers or more, high pore volume and porosity, as well as low refractive index and dielectric constant can be obtained. When the pores of the shell of the hollow particles are 10 nanometers or less, the hollow particles have good particle strength, and when used as a coating composition to prepare a coating film, the internal pores are unlikely to be filled, and good abrasion resistance and antireflection properties can be obtained. From the viewpoint of refractive index and dielectric constant, it is more preferably 0.5 to 4 nanometers.
[0051] In one embodiment of the hollow silica sol according to the present invention, the pore volume of the hollow silica particles is, for example, 0.15 to 1.0 cm 3 / g. The pore volume of the hollow silica particles may be 0.15 cm 3 / g or more, the particles can have a low refractive index. 3 If the particle size is less than or equal to 1 / g, the particle can have sufficient strength.
[0052] The pore size and pore volume can be measured by static adsorption, for example, using a Quadrasorb evo surface area and porosity analyzer (Quantachrome Instruments, USA) at 77 K. The pore size and pore volume on the shell of hollow silica particles are measured using an isothermal adsorption curve and the Barrett-Joyner-Halenda (BJH) model.
[0053] In one embodiment of the hollow silica sol according to the present invention, the refractive index of the hollow silica particles may be, for example, 1.10 to 1.45. When the refractive index of the hollow silica particles is 1.10 or more, the hollow particles have good hardness and strength. When the refractive index of the hollow silica particles is 1.45 or less, the hollow silica particles have a relatively low refractive index and exhibit excellent performance in an antireflection layer.
[0054] In one embodiment of the hollow silica sol according to the present invention, the hollow silica particles have a relative dielectric constant of, for example, 1.6 to 2.2. When the hollow silica particles have a relative dielectric constant of 1.6 or more, the particles have sufficient strength in a composite dielectric. From the viewpoint of excellent dielectric properties and low dielectric loss, the hollow silica particles have a relative dielectric constant of 2.2 or less, more preferably 2.0 or less.
[0055] In one embodiment of the hollow silica sol according to the present invention, the particle size of the hollow silica particles is, for example, 15 to 1000 nm. From the viewpoint of the transparency of the optical coating layer to be formed, the particle size is more preferably 20 to 500 nm, and further preferably 20 to 100 nm.
[0056] In one embodiment of the hollow silica sol according to the present invention, the polydispersity index (PDI) of the hollow silica particles is, for example, 0.05 to 0.3. The polydispersity index is obtained from the test data of the hollow silica sol by dynamic light scattering (DLS). The lower the PDI, the more uniform the size distribution of the hollow particles tends to be and the more monodisperse they are. When the PDI is 0.3 or less, the hollow silica particles have a uniform size distribution, and after being prepared as a coating layer, the coating layer surface has low roughness and has better abrasion resistance.
[0057] By appropriately setting the pores with suitable sizes and the thickness of the shell layer, it is ensured that the hollow particles have a relatively low refractive index with sufficient porosity, and other substances cannot enter the internal cavity through the pores of the hollow particle shell, so that the hollow particles always have excellent anti-reflective properties in coating compositions, coating layers, and products containing the coating layers.
[0058] In one embodiment of the hollow silica sol according to the present invention, the content of hollow silica particles is preferably in the range of 0.5% by mass to 70% by mass. From the viewpoint of efficiency in forming a coating layer, the content of hollow silica particles in the hollow silica sol is preferably 0.5% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more. From the viewpoint of storage stability and suitable viscosity of the hollow silica sol, the content of hollow silica particles in the hollow silica sol is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less.
[0059] The dispersion medium contained in the hollow silica sol is water, an organic solvent, or a combination of both. The organic solvent means an organic compound that contains carbon atoms and is flowable. The function of the dispersion medium is to allow the hollow silica particles to exist in the state of individual particles in the environment provided by the dispersion medium, and to avoid the hollow silica particles from agglomerating in the dry state, which affects the optical transparency of the final coating layer and the product. Examples of organic solvents include methanol, ethanol, isopropanol, butanol, ethyl acetate, butyl acetate, acetone, butanone, methyl isobutyl methyl ketone, heptane, hexane, cyclohexane, heptane, octane, nonane, ethylene glycol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, tetrahydrofuran, N,N-dimethylformamide, and N,N-dimethylacetamide, but there is no particular limit as long as they do not affect the performance of the hollow silica sol and hollow silica particles.
[0060] [Preparation method of hollow silica sol] The method for preparing the hollow silica sol is as follows: an intermediate product producing step of mixing a silicon source, a first solvent, a first catalyst and an active compound, reacting them at a temperature in the range of 0 to 150°C, and then removing those having a boiling point of less than 300°C to obtain a liquid silicone intermediate product P1; a hollow silica production step of dispersing the silicone intermediate product P1 in a second solvent, adding a second catalyst, and reacting at a temperature in the range of 0 to 95°C to obtain a hollow silica sol; The method includes a hydrothermal treatment step in which, after washing as necessary, hydrothermal treatment is performed within a range of 30 to 300°C.
[0061] The above steps will be described below in order.
[0062] [Intermediate product generation process] In the intermediate product production step, alkoxy groups in the silicon source are hydrolyzed in the presence of a first solvent under the catalytic action of a first catalyst to produce hydroxy groups (Si-OH), and the produced hydroxy groups (Si-OH) undergo further condensation reaction or react with hydroxy groups in an active compound to produce a high-boiling liquid silicone intermediate product and a low-boiling substance (a substance with a boiling point of less than 300°C) as a by-product. By removing the low-boiling substance to purify the intermediate product, the molecular weight distribution of the intermediate product becomes narrower and the chemical properties become more uniform.
[0063] The composition of the silicon source is not particularly limited, as long as it contains an alkoxy group, can be hydrolyzed to produce a hydroxy group (Si-OH), and can be further condensed to produce a flowable intermediate product.
[0064] Preferably, the silicon source is one or more silane monomers represented by formula I below, or a polyalkoxysiloxane oligomer having the empirical formula represented by formula II below. R 1 4-n Si(OR 2 ) n Formula I (wherein n is 1, 2, 3 or 4; R 1 is an alkyl group, a vinyl alkyl group, a vinyl group, an epoxy alkyl group, a phenyl group, a styryl alkyl group, a methacryloxy alkyl group, an acryloxy alkyl group, an amino alkyl group, a urethane group, a chloro alkyl group, a mercapto alkyl group, an isocyanato alkyl group, or a hydroxy alkyl group; R 1 If there are multiple R 1 may be the same or different from each other, R 2 is an alkyl group having 1 to 6 carbon atoms, and R 2 If there are multiple R 2 may be the same or different.) SiO m (OR 3 ) 4-2m Formula II (where 0 < m < 2, m is an integer or a non-integer, R 3 is an alkyl group having 1 to 6 carbon atoms, and when there are a plurality of R 3 s, each R 3 may be the same as or different from each other.)
[0065] In the above formula, as the "alkyl group" in the alkyl group, vinylalkyl group, vinyl group, epoxyalkyl group, phenyl group, styrylalkyl group, methacryloxyalkyl group, acryloxyalkyl group, aminoalkyl group, urethane group, chloroalkyl group, mercaptoalkyl group, isocyanatoalkyl group, or hydroxyalkyl group represented by R 1 , for example, an alkyl group having 1 to 22 carbon atoms can be mentioned, and it may be an alkyl group having 1 to 10 carbon atoms, and further may be an alkyl group having 1 to 8 carbon atoms.
[0066] Examples of the "alkyl group having 1 to 8 carbon atoms" include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1-ethylpropyl group, a 1,2-dimethylpropyl group, a hexyl group, an n-heptyl group, an n-octyl group, etc., and are not particularly limited.
[0067] Examples of the polyalkoxysiloxane oligomer having the empirical formula represented by the above formula II include commercially available Silicon 40, Silicon 48, Silicon 51, Silicon 53, Silicon 63, etc.
[0068] As the silicon source, one or more of the silane monomers having the structure shown in the above formula I, or one or more of the polyalkoxysiloxane oligomers shown in the above formula II may be used, or a combination of both may be used.Preferably, the silicon source is at least one selected from tetraethyl silicate, tetramethyl silicate, vinyl triethoxy silane, methyl triethoxy silane, 3-(methacryloyloxy)propyl triethoxy silane, silicon 40, silicon 48, and silicon 51.
[0069] The first solvent is preferably water or a mixed solvent of water and an organic solvent, more preferably a mixed solvent of water and an organic solvent, and is, for example, at least one selected from aqueous methanol, aqueous ethanol, aqueous isopropanol, aqueous butanol, aqueous ethylene glycol, aqueous ethylene glycol monobutyl ether, aqueous propylene glycol, and aqueous propylene glycol methyl ether.
[0070] The weight ratio of water and silicon source contained in the first solvent is preferably 0.001:1 or more and less than 0.5:1. In the intermediate product generation step, the alkoxy group in the silicon source is hydrolyzed in contact with water, and further condenses to form an intermediate product containing a Si-O-Si structure. When the weight ratio is 0.001:1 or more, the molecular weight of the intermediate product obtained is sufficiently high, and the hydrophilicity after reaction with the active compound is not too strong, so that surface activity can be generated. When the weight ratio is less than 0.5:1, some of the alkoxy group in the silicon source has not yet been completely reacted, which is favorable for the subsequent reaction with the active compound.
[0071] In addition, the weight ratio of water to silicon source is one of the factors that affect the thickness of the shell layer of the hollow silica particles that are the final product, and the thickness of the shell layer of the hollow silica particles increases as the weight ratio of water to silicon source increases.From the viewpoint of ensuring the sufficient thickness of the shell layer of the hollow silica particles and obtaining sufficient strength of the hollow silica particles, the weight ratio of water to silicon source is preferably 0.01:1 or more.From the viewpoint of ensuring that the shell layer of the hollow silica particles is not too thick and has a low refractive index, the weight ratio of water to silicon source is preferably 0.25:1 or less.
[0072] In the first solvent, the solvent other than water is used to mix water and silicon source quickly and uniformly.The amount of the solvent added is not particularly limited, but from the viewpoint of saving production cost, it is preferable that the amount of the solvent used is such that water and silicon source can be mixed uniformly.
[0073] The first catalyst is an acid, a base, or a metal alkoxide, a metal carboxylate. Examples of such acids include, but are not limited to, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, oxalic acid, acidic cation exchange resins, etc. Examples of such bases include, but are not limited to, ammonia water, organic amines, sodium hydroxide, potassium hydroxide, sodium bicarbonate, sodium carbonate, etc. Examples of such metal alkoxides include, but are not limited to, titanium alkoxides, aluminum alkoxides, zirconium alkoxides, etc. Examples of such metal carboxylates include, but are not limited to, tin acetate, aluminum acetate, zirconium acetate, etc. From the viewpoint of reaction controllability, the first catalyst is preferably an acid or titanium alkoxide. Examples of titanium alkoxides include, but are not limited to, tetramethoxytitanium, tetraethoxytitanium, tetrapropoxytitanium, etc.
[0074] The weight ratio of the first catalyst to the silicon source is preferably 0.001 to 0.5: 1. Controlling the weight ratio to 0.5: 1 or less is advantageous for preventing the formation of a gel-like solid due to an excessively fast reaction rate, while controlling the weight ratio to 0.001: 1 or more is advantageous for improving catalyst efficiency and obtaining a suitable reaction rate.
[0075] The active compound means a compound that plays a role in improving the hydrophilicity of silicone intermediate product.For example, such an active compound includes those that have at least one OH group, have a molecular weight of more than 150, and have an HLB value calculated by the following formula III of more than 5. HLB=20×M h / M formula III (In the formula, M h is the molecular weight of the hydrophilic portion of the active compound, and M is the molecular weight of the active compound.
[0076] The active compound can be a single substance or a mixture of two or more.The active compound can be, for example, one or two or more selected from polyacrylic acid, polyethylene glycol, polyethylene glycol monoether, polyvinyl alcohol, polyglycerin, and copolymers of ethylene oxide and propylene oxide.When the HLB value of the active compound calculated by formula III is less than 5, the active compound cannot impart suitable hydrophilicity to the silicone intermediate product, and hollow silica particles cannot be obtained in the subsequent process.
[0077] The weight ratio of the active compound to the silicon source may be, for example, (0.05 to 0.5):1. By controlling the mass ratio to 0.05:1 or more, the obtained silicone intermediate product has sufficient hydrophilicity, is unlikely to aggregate in a water-containing solvent, and can form particles having a hollow structure. By controlling the mass ratio to 0.5:1 or less, the obtained silicone intermediate product has a part that is hydrophobic, has suitable surface activity, and can form hollow particles in a subsequent process.
[0078] The reaction temperature in the intermediate product production step is 0 to 150° C., and preferably 60 to 100° C. The reaction time is, for example, 1 to 24 hours, and preferably 5 to 15 hours. From the viewpoint of achieving both the completeness of the reaction and the reaction efficiency, it is more preferably 8 to 10 hours.
[0079] During the reaction process of the intermediate product formation step, the alkoxy groups of the silicon source undergo hydrolysis and condensation to form the silicone intermediate product P1, and also form some by-products with boiling points of less than 300° C. Examples of such by-products with boiling points of less than 300° C. include intermediate products with molecular weights of less than 500, and small molecular alcohol compounds formed by hydrolysis and condensation of alkoxy groups.
[0080] The removal of by-products with a boiling point of less than 300°C has an important effect on the preparation of hollow silica particles. By removing the alcohol-based compounds as by-products, the hydrolysis and condensation of the silicon source and the condensation with active compounds containing hydroxyl groups can proceed in the forward direction to obtain intermediate products with higher molecular weights, which can finally form hollow silica particles. By removing intermediate products with a molecular weight of less than 500, the particle size of the hollow silica particles prepared becomes more uniform and the size can be controlled more easily.
[0081] The method for removing the low boiling by-products may be, for example, one or a combination of atmospheric distillation, reduced pressure distillation, thin film evaporation, or rotary evaporation. The removal of the low boiling by-products may be carried out together with the hydrolysis and condensation reactions, and if the distillation of liquid is observed during the reaction, it indicates that the by-products have been removed. After the heating reaction is completed, the removal of the first reaction by-products may be further carried out to fully remove the by-products. During the removal process, if no distillation of liquid is observed or the mass of the liquid in the collection bottle does not change after a certain period of time, it is considered that the by-products have been completely removed, and what remains is the silicone intermediate product P1.
[0082] [Hollow silica production process] In the hollow silica production step, the silicone intermediate product P1 is dispersed in a second solvent, a second catalyst is added, and the mixture is reacted at a temperature in the range of 0 to 95° C. to obtain a hollow silica sol.
[0083] The second solvent is water, or a combination of water and a hydrophilic solvent, or a combination of water and a hydrophobic solvent. Such hydrophilic solvents include organic solvents that are miscible with water, such as alcohols, ketones, and ethers. Such hydrophobic solvents include organic solvents such as alkanes, aromatic hydrocarbons, and esters.
[0084] When the silicone intermediate product P1 is dispersed in the second solvent, the silicone intermediate product P1 forms a vesicle-like structure with the second solvent. Both the inside and outside of the vesicle are water-containing solvents, and the silicone intermediate product P1 is concentrated at the interface. The silicone intermediate product P1 is rapidly hydrolyzed and condensed by the action of the second catalyst to form hollow silica particles with a dense silica shell layer. This results in a sol containing monodispersed hollow silica particles.
[0085] On the other hand, the silicone intermediate product is hydrolyzed and condensed to silica by the action of the second catalyst, and at the same time releases a small molecular alcohol. When the size of the vesicle is approximately constant, the release of the small molecular alcohol introduces a sufficient number of pores into the silica shell.
[0086] By adjusting the type and amount of the second catalyst, the pore size, pore volume, and refractive index of the hollow particles can be adjusted.Usually, when a base is used as a catalyst, the pores formed are larger in size, the pore volume is higher, and the refractive index is lower than when an acid is used as a catalyst.
[0087] The second catalyst is, for example, an acid or a base. The acid may be an organic acid or an inorganic acid. Examples of inorganic acids include hydrochloric acid, nitric acid, and sulfuric acid, and examples of organic acids include formic acid, acetic acid, and acrylic acid. The base may be an inorganic base or an organic base. Examples of inorganic bases include sodium hydroxide, potassium hydroxide, and aqueous ammonia, and examples of organic bases include triethylamine. In addition, in the case of an acid salt or a basic salt that is in the form of a salt but shows acidity or basicity, if it can act as a second catalyst to react the silicone intermediate product to produce hollow silica particles, it is considered to belong to the second catalyst. The second catalyst may be the same as or different from the first catalyst.
[0088] The weight ratio of the second catalyst to the silicone intermediate may be, for example, (0.05-2:1).
[0089] In the hollow silica particle production step, from the viewpoint of obtaining suitable dispersion viscosity and production efficiency, the weight percentage of the silicone intermediate product P1 relative to the second solvent is preferably 1 to 60%.
[0090] The hollow silica particle generation process provides hollow silica sol with good dispersibility. However, since it does not undergo surface densification treatment, there are excess hydroxyl groups and defects. If the solid content of such primary hollow silica sol is high, the viscosity increases over time and it gels, which affects its subsequent use. In addition, the shell of the silica balloon is relatively soft and has many surface defects, which makes it poor in abrasion resistance when used as a subsequent coating composition or coating product, and the hollow structure is easily filled, which may affect anti-reflection performance, dielectric performance, etc.
[0091] [Hydrothermal treatment process] The hydrothermal treatment process is carried out at a temperature of 30°C to 300°C. The hydrothermal treatment makes the shell layer of the hollow silica particles more uniform and dense, the particles become more spherical due to surface tension, and the mechanical strength is greatly improved. Compared with hollow silica sol that has not been hydrothermally treated, the hollow silica sol after the hydrothermal treatment process still maintains a low viscosity even when the solid content is relatively high, and has improved thermal stability and storage stability. In addition, the shell layer of the hollow silica particles becomes denser, the surface defects are reduced, and the hardness and abrasion resistance of the coating layer formed are improved. In addition, when used in anti-reflective coatings, a resin with a relatively high refractive index cannot enter the inside of the hollow particles, so a coating film with a high anti-reflective effect is obtained.
[0092] By adjusting the ratio of groups such as hydroxyl groups on the surface of hollow silica particles by hydrothermal treatment so that the obtained hollow silica sol satisfies the ranges of Q1, Q2, Q3, and Q4 of the hollow silica sol according to the present invention, the hollow silica particles contained in the obtained hollow silica sol have few defects, a dense surface structure, excellent mechanical performance, low sol viscosity, and other properties.In addition, the hollow silica particles are provided with sufficient hydroxyl groups on the surface to make them easy to disperse in water and other solvents, form a stable silica sol, and facilitate subsequent surface functionalization treatment, and can be applied to different types of coating compositions.
[0093] The hydrothermal temperature of the hydrothermal process is 30°C to 300°C. When the hydrothermal temperature is 30°C or higher, the shell of the silica balloon can be effectively densified, and when used as a paint and a coating layer, the coating film property, anti-reflection property and strength of the coating layer can be effectively improved. When the hydrothermal temperature exceeds 300°C, the hollow particle surface cannot be further densified, and the performance of the paint and coating layer formed cannot be further improved, and at the same time, the hollow particles may aggregate and precipitate from the sol, which may cause problems in further use. From the viewpoint of the water resistance, weather resistance and abrasion resistance of the coating layer formed, the hydrothermal treatment temperature is preferably 100°C to 200°C.
[0094] Before the hydrothermal treatment step, a well-known washing step such as ultrafiltration, centrifugation, ion exchange resin, etc. may be optionally carried out to remove other substances and ions other than silica that may be present in the hollow silica sol. The washing step makes the hollow silica sol have higher purity and better stability.
[0095] The method for preparing hollow silica sol according to the present invention does not require a step of removing the internal template by conventional means such as high-temperature calcination, solvent etching, or dissolution with an acid or alkali, and can provide a hollow particle dispersion liquid that is excellent in monodispersity and free of secondary aggregation.
[0096] In addition, according to the method for preparing hollow silica sol of the present invention, hollow silica particles having high mechanical strength and a uniform and dense shell layer can be prepared by the hydrothermal treatment process. When the particles are used in a coating composition or coating layer, the coating layer can be provided with excellent water resistance, abrasion resistance, weather resistance and anti-reflection properties.
[0097] The hollow silica sol obtained as above can be combined with an adhesive to form a coating composition, which is widely used to form an anti-reflective coating layer. Alternatively, various additives can be added to the coating composition according to the performance needs of the coating layer to be formed. Furthermore, the hollow silica sol can be dried and stored as a powder of hollow silica particles.
[0098] Furthermore, according to the method for preparing hollow silica sol of the present invention, the sol has excellent low dielectric properties without introducing metal ions.
[0099] The shell layer of the hollow particles contained in the hollow silica sol obtained by the hollow silica sol preparation method contains pore channels that can be used for coating and sustained release.
[0100] Optionally, the method for preparing the hollow silica sol according to the present invention may further include the following steps:
[0101] Solvent replacement process In the solvent replacement step, the original solvent in the obtained hollow silica sol is replaced with an organic solvent in whole or in part using equipment such as an ultrafiltration membrane, a rotary evaporator, or a centrifuge to obtain an organic sol of hollow silica. The above "part" may be, for example, 20% or more, 40% or more, 60% or more, 80% or more, 90% or more, or 99% or more.
[0102] The solvent used for the substitution may be one or a mixture of two or more kinds. The hollow silica sol that has undergone the solvent substitution process can be applied to most coating systems, and the resulting coating composition has excellent dispersibility, does not cause aggregation in the resulting coating layer and product, and imparts good optical transparency to the coating layer and prevents whitening of the coating layer.
[0103] For example, when the solvent of the hollow silica sol before the substitution is water, the water in the sol can be substituted with methanol to obtain a methanol sol of hollow silica.
[0104] In another embodiment, for example, when the solvent of the hollow silica sol before the substitution is methanol, a part of the methanol can be substituted with acetone to obtain a methanol / acetone sol of hollow silica.
[0105] Surface modification process The hollow silica particle surfaces are modified by adding one or more members selected from the group consisting of silane represented by the following formula IV and / or its partial hydrolyzate, hexamethyldisiloxane, and hexamethyldisilazane to the hollow silica sol. R 4 p -Si-X 4-p Formula IV (wherein p is 0, 1, 2 or 3; R 4 is selected from an alkyl group, a vinyl alkyl group, an epoxy alkyl group, a styryl alkyl group, a methacryloxy alkyl group, an acryloxy alkyl group, an amino alkyl group, a urethane group, a chloro alkyl group, a mercapto alkyl group, an isocyanato alkyl group, or a hydroxy alkyl group; R 4If there are multiple R 4 may be the same or different, R 4 may be substituted with fluorine atoms, X is selected from an alkoxy group having 1 to 6 carbon atoms, halogen, or hydrogen, and when there are multiple X's, each X may be the same or different.
[0106] R 4 Examples of the "alkyl group" in "alkyl group, vinyl alkyl group, vinyl group, epoxy alkyl group, phenyl group, styryl alkyl group, methacryloxy alkyl group, acryloxy alkyl group, amino alkyl group, urethane group, chloro alkyl group, mercapto alkyl group, isocyanato alkyl group, or hydroxy alkyl group" include alkyl groups having 1 to 22 carbon atoms, and may be alkyl groups having 1 to 10 carbon atoms, or may be alkyl groups having 1 to 8 carbon atoms.
[0107] Examples of the "alkyl group having 1 to 8 carbon atoms" include, but are not limited to, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1-ethylpropyl group, a 1,2-dimethylpropyl group, a hexyl group, an n-heptyl group, and an n-octyl group.
[0108] By adding one or more selected from the group consisting of silane and / or its partial hydrolyzate represented by formula IV, hexamethyldisiloxane and hexamethyldisilazane to the hollow silica sol to modify the surface of the hollow silica particles, the surface of the hollow silica particles can be modified with organic groups, and the hollow silica exhibits better dispersion stability in a specific organic solvent. This further increases the affinity with the adhesive in the paint, and the interaction with the adhesive becomes stronger during the coating layer curing process, so that the coating layer can be given better adhesion, hardness and abrasion resistance.
[0109] In formula IV, R 4 By substituting some or all of the hydrogen atoms in with fluorine atoms, the refractive index of the hollow silica particles can be further reduced. In addition, the surface of the hollow particles is made more hydrophobic, so that when used in a coating composition, it can impart excellent fingerprint resistance, slipperiness, and stain resistance to the coating layer, and can provide excellent abrasion resistance.
[0110] The surface modification step may be carried out at any stage after the hollow silica production step, and / or after the hydrothermal treatment step, and / or after the solvent replacement step.
[0111] The order of the hydrothermal treatment step, the solvent replacement step and the surface modification step may be selected randomly, or any one or more of the steps may be repeated, as long as the stability of the hollow silica sol and its dispersion in the coating composition are not impaired.
[0112] Alternatively, in the method for preparing a hollow silica sol according to the present invention, hollow silica powder can be obtained by drying or calcining after any one of the hollow silica production step, the hydrothermal treatment step, the solvent replacement step, and the surface modification step.
[0113] The method for preparing hollow silica sol according to the present invention does not use any hard or soft template, but utilizes the self-organizing behavior of silicone intermediate products in water to produce an aqueous dispersion of hollow silica particles. There is no need to remove the template by high-temperature baking, solvent etching, dissolving with acid or alkali, and the aggregation of hollow particles is avoided. The hydrothermal treatment makes the hollow particle surface more dense, the shell layer more uniform, the mechanical strength more improved, and the weather resistance more improved; the solvent replacement gives a hollow silicone sol with a different dispersion system; the surface modification further improves the dispersion stability of hollow particles in organic solvents and the affinity with organic resins, giving the coating composition and coating layer excellent optical performance, mechanical performance, and weather resistance.
[0114] In addition, the hollow silica sol prepared by the method of the present invention has excellent refractive index and can be used for anti-reflection coating, and has better low dielectric properties because no metal ions are introduced. In addition, due to the pore structure on the shell, the hollow silica particles can be used to support and release active molecules.
[0115] [Paint composition] The coating composition according to the present invention comprises the hollow silica sol according to the present invention, an adhesive, and a solvent and an auxiliary that are used as necessary.
[0116] The adhesives include inorganic adhesives including precursor compounds known to those skilled in the art that can form the corresponding inorganic oxides by hydrolysis-condensation reactions, such as metal alkoxides, metal salts, siloxanes, silicates, and mixtures thereof, as well as various polymers known to those skilled in the art, including acrylate monomers, methacrylate monomers, and various oligomers derived therefrom, such as (meth)acrylate oligomers, polyurethane (meth)acrylate oligomers, epoxy (meth)acrylate oligomers, polyester (meth)acrylate oligomers, and radically curable unsaturated polyesters or polyurethanes of acrylates, methacrylates, and organic adhesives including monomers and oligomers that can be cured by heat or radiation (e.g., UV, electron beam).
[0117] Examples of the solvent include water, alcohols, ketones, ethers, esters, nitrogen-containing compounds, and sulfur-containing compounds. Examples of the alcohols include methanol, ethanol, and isopropanol. Examples of the ketones include acetone and methyl ethyl ketone. Examples of the ethers include tetrahydrofuran and 1,4-dioxane. Examples of the ethers include ethyl acetate and methyl acetate. Examples of the nitrogen-containing compounds include N,N-dimethylacetamide and N,N-dimethylformamide. Examples of the sulfur-containing compounds include dimethyl sulfoxide.
[0118] The coating composition according to the present invention may contain hollow particles or solid particles other than the hollow particles according to the present invention, so long as the effects of the present invention are not impaired.
[0119] The coating composition of the present invention may further include other auxiliary agents, such as, for example, thermal initiators, photoinitiators, antistatic agents, leveling agents, wetting agents, defoamers, pigments, dyes, ultraviolet shielding agents, infrared shielding agents, antioxidants, and anti-fingerprint agents.
[0120] In the coating composition according to the present invention, the weight ratio of the hollow silica particles to the adhesive may be, for example, 0.1:1 to 5:1, preferably 0.5:1 to 3:1, and more preferably 0.8:1 to 2:1. If the hollow particle / adhesive ratio is too low, the antireflection properties of the coating layer tend to be insufficient, whereas if it is too high, the antireflection properties cannot be further improved, and the mechanical performance and weather resistance of the coating layer tend to deteriorate.
[0121] The coating composition according to the present invention contains the hollow particles according to the present invention, which have a low refractive index and high particle strength, and therefore can form a coating film that has excellent anti-reflection effect and is highly abrasion resistant and hard.
[0122] [product] The product according to the present invention comprises a substrate and a coating layer on the substrate surface. The coating layer may be one or more layers, and at least one of the coating layers is formed by curing the coating composition according to the present invention.
[0123] The coating layer can be formed by applying the coating composition of the present invention to a substrate and drying the applied layer, which may be further heated, baked or irradiated with radiation.
[0124] Examples of the substrate include, but are not limited to, glass, transparent polymers, and metals.
[0125] Examples of the coating method include, but are not limited to, bar coating, knife coating, spin coating, dip coating, roll coating, flow coating, spray coating, slit coating, and microgravure coating.
[0126] The above-mentioned product according to the present invention has a coating layer made of the coating composition according to the present invention, and therefore has good anti-reflection effect, good abrasion resistance, and high hardness. EXAMPLES
[0127] In order to describe the present invention in more detail, the present invention will be further described in combination with preferred embodiments. Those skilled in the art can understand that the contents specifically described below are illustrative rather than restrictive, and do not limit the protection scope of the present invention.
[0128] In the present invention, the preparation methods are conventional methods unless otherwise specified, the raw materials used are those available from open commercial channels unless otherwise specified, % means % by weight, and temperatures are in degrees Celsius (°C).
[0129] The specific meanings of the symbols and the measurement conditions in each example are as follows:
[0130] Solid content: measured by a solid content measuring device Precisa XM60, and indicates the solid content when baked at 150°C until a constant amount is reached.
[0131] Viscosity: The temperature is set at 25°C, the solid content of the hollow silcasol is fixed at 20%, and it is measured by a rotational viscometer.
[0132] Average particle size: 100 particles are randomly selected from the corresponding TEM photograph, the particle size of each particle is measured, and the average value of the measured particle sizes is taken as the average particle size of the particles.
[0133] Shell layer thickness: Randomly select 100 particles from the corresponding TEM photograph, measure the shell thickness of each particle, and take the average value of the measured shell layer thicknesses as the shell layer thickness.
[0134] Measurement of Q1, Q2, Q3, and Q4 ratios: After drying and powdering the hollow silica sol, the ratios were measured using a nuclear magnetic resonance (Bruker AVIII HD500 spectrometer). 29 A Si NMR spectrum is measured, and then a resonance peak area Q1 having a chemical shift of -78 to -88 ppm, a resonance peak area Q2 having a chemical shift of -88 to -98 ppm, a resonance peak area Q3 having a chemical shift of -98 to -108 ppm, and a resonance peak area Q4 having a chemical shift of -108 to -117 ppm are integrated, respectively, to calculate the values of Q1, Q2, Q3, and Q4.
[0135] Measurement of polydispersity: A dynamic light scattering meter (Malven, Zetasizer Nano, ZS90-2027) is adopted to measure the dispersion and obtain the particle size distribution curve and polydispersity results.
[0136] Pore size distribution, pore volume and porosity: Using a Quadrasorb evo specific surface area and porosity analyzer (Quantachrome Instruments, USA), static adsorption BET is measured by N2 adsorption test under 77 K conditions. The pore size distribution, pore volume and porosity are measured using an isothermal adsorption curve and the Barrett-Joyner-Halenda (BJH) model, and the refractive index RI is calculated according to the following refractive index calculation formula:
[0137]
number
[0138] Dielectric constant: Dielectric constant e ris measured in an electrostatic field as follows: First, the capacitance C0 of the capacitor is measured when the space between the two plates is a vacuum under standard atmospheric pressure, and then the capacitance C after adding a dielectric between the two plates with the distance between the plates of the capacitor constant is measured. x Measure the relative dielectric constant e according to the following formula: r Calculate. e r =C x / C0
[0139] Example 1 208 g of tetraethoxysilane, 20 g of water, 5 g of hydrochloric acid (concentration 37%), and 30 g of polyethylene glycol (molecular weight 500) were mixed uniformly, heated to 85°C with stirring, and reacted for 8 hours. After that, the temperature was further raised to 135°C and a vacuum was applied until no more liquid was extracted, yielding 156 g of a transparent silicone intermediate product with a certain viscosity.
[0140] After mixing the obtained silicone intermediate product (156 g) with 500 g of water, stirring was started and 20 g of aqueous ammonia (mass concentration: 25%) was quickly added at the same time. The mixture was allowed to react for 24 hours with continued stirring to obtain a hollow silica sol with a solid content of 9.2%.
[0141] The hollow silica sol was washed with an ultrafiltration membrane and then subjected to a hydrothermal treatment at 200° C. for 12 hours to obtain hollow silica sol 1.
[0142] A transmission electron microscope (TEM) photograph of the hollow silica particles in the obtained hollow silica sol 1 is shown in FIG. 1. The average particle diameter was measured to be 55 nanometers, and the thickness of the shell layer was 5.5 nanometers.
[0143] The results of dynamic light scattering (DLS) such as size, PDI, ratio of Q1 to Q4, pore size distribution, pore volume, and dielectric constant are shown in Table 1.
[0144] Example 2 Silicon 48 (Gelest Int., empirical formula: SiO 1.12 (OCH2CH3) 1.76A mixture of 120 g of ethyl acetate, 60 g of ethanol, 2.5 g of water, 1.0 g of aqueous ammonia (concentration 25%), and 25 g of polyethylene glycol monomethyl ether (molecular weight 500) was uniformly mixed and heated to 65°C with stirring. After reacting for 8 hours, the mixture was further heated to 135°C and vacuum was applied until no more liquid was extracted, yielding 150 g of a transparent silicone intermediate product having a certain viscosity.
[0145] 150 g of the obtained silicone intermediate product was mixed with 1,000 g of water, and then stirring was started. At the same time, 50 g of ammonia water (mass concentration 25%) was quickly added. The mixture was allowed to react for 24 hours with continued stirring to obtain a hollow silica sol with a solid content of 4.8%.
[0146] The hollow silica sol was washed with an ultrafiltration membrane and then subjected to a hydrothermal treatment at 150° C. for 24 hours to obtain hollow silica sol 2.
[0147] A transmission electron microscope (TEM) photograph of the hollow silica particles in the obtained hollow silica sol 2 is shown in FIG. 2. The average particle diameter was measured to be 70 nanometers, and the thickness of the shell layer was 6.5 nanometers.
[0148] The results of dynamic light scattering (DLS) such as size, PDI, ratio of Q1 to Q4, pore size distribution, pore volume, and dielectric constant are shown in Table 1.
[0149] Example 3 145 g of tetramethoxysilane, 5 g of methyltriethoxysilane, 75 g of isopropanol, 25 g of water, 5 g of nitric acid (concentration 63%), and 40 g of polyethylene glycol monomethyl ether (molecular weight 500) were mixed uniformly and heated to 85°C with stirring. After reacting for 8 hours, the temperature was further increased to 135°C and a vacuum was applied until no more liquid was extracted, yielding 160 g of a transparent silicone intermediate product having a certain viscosity.
[0150] After mixing 160 g of the obtained silicone intermediate product with 500 g of water, stirring was started and at the same time 20 g of ammonia water (mass concentration 25%) was quickly added. The mixture was allowed to react for 24 hours with continued stirring to obtain a hollow silica sol with a solid content of 8.6%.
[0151] The hollow silica sol was washed with an ultrafiltration membrane and then subjected to a hydrothermal treatment at 120° C. for 12 hours to obtain hollow silica sol 3.
[0152] A transmission electron microscope (TEM) photograph of the hollow silica particles in the obtained hollow silica sol 3 is shown in FIG. 3. The average particle diameter was measured to be 40 nanometers, and the thickness of the shell layer was 4.5 nanometers.
[0153] The results of dynamic light scattering (DLS) such as size, PDI, ratio of Q1 to Q4, pore size distribution, pore volume, and dielectric constant are shown in Table 1.
[0154] Comparative Example 1 Hollow silica sol 4 was obtained in the same manner as in Example 1, except that the hydrothermal treatment in Example 1 was not carried out.
[0155] A transmission electron microscope (TEM) photograph of the obtained hollow silica particles 4 is shown in Figure 4. The results of the size, PDI, ratio of Q1 to Q4, pore size distribution, pore volume, dielectric constant, etc. measured by dynamic light scattering (DLS) are shown in Table 1.
[0156] Comparative Example 2 Hollow silica sol 5 was obtained in the same manner as in Example 2, except that the hydrothermal treatment in Example 2 was not carried out.
[0157] A transmission electron microscope (TEM) photograph of the obtained hollow silica particles 5 is shown in FIG. The results of dynamic light scattering (DLS) such as size, PDI, ratio of Q1 to Q4, pore size distribution, pore volume, and dielectric constant are shown in Table 1.
[0158] Comparative Example 3 Hollow silica sol 6 was obtained in the same manner as in Example 3, except that the hydrothermal treatment in Example 3 was not carried out.
[0159] A transmission electron microscope (TEM) photograph of the obtained hollow silica particles 6 is shown in Figure 6. The results of the size, PDI, ratio of Q1 to Q4, pore size distribution, pore volume, dielectric constant, etc. measured by dynamic light scattering (DLS) are shown in Table 1.
[0160] Example 4 The solvent of the hollow silica sol 1 prepared in Example 1 was replaced with isopropanol using an ultrafiltration membrane, and the mixture was concentrated to obtain hollow silica isopropanol sol 7 having a solid content of 20%.
[0161] 50 g of hollow silica isopropanol sol 7 was taken, 2 g of γ-methacryloyloxypropyltrimethoxysilane and 0.2 g of water were added, and the mixture was heated to 80°C and reacted for 12 hours. After that, 2 g of trimethyl orthoformate was added and reacted to obtain hollow silica modified isopropanol sol 8 with a solid content of 20.5%.
[0162] Example 5 The solvent of the hollow silica sol 2 prepared in Example 2 was replaced with isopropanol using an ultrafiltration membrane, and the mixture was concentrated to obtain a hollow silica isopropanol sol 9 having a solid content of 20%.
[0163] 50 g of hollow silica isopropanol sol 9 was taken, 2 g of γ-methacryloyloxypropyltrimethoxysilane and 0.2 g of water were added, and the mixture was heated to 80°C and reacted for 12 hours. After that, 2 g of trimethyl orthoformate was added and reacted to obtain hollow silica modified isopropanol sol 10 with a solid content of 20.5%.
[0164] Example 6 The solvent of the hollow silica sol 3 prepared in Example 3 was replaced with isopropanol using an ultrafiltration membrane, and the mixture was concentrated to obtain a hollow silica isopropanol sol 11 having a solid content of 20%.
[0165] 50 g of hollow silica isopropanol sol 11 was taken, 2 g of γ-methacryloyloxypropyltrimethoxysilane and 0.2 g of water were added, and the mixture was heated to 80°C and reacted for 12 hours. After that, 2 g of trimethyl orthoformate was added and reacted to obtain hollow silica modified isopropanol sol 12 with a solid content of 20.5%.
[0166] Comparative Example 4 Instead of the hollow silica sol 1 in Example 4, the hollow silica sol 4 obtained in Comparative Example 1 was used, and otherwise the same procedure as in Example 4 was repeated to obtain a hollow silica-modified isopropanol sol 13 having a solid content of 20.5%.
[0167] Comparative Example 5 Hollow silica sol 5 obtained in Comparative Example 2 was used instead of hollow silica sol 2 in Example 5, and the rest was the same as in Example 5 to obtain hollow silica-modified isopropanol sol 14 having a solid content of 20.5%.
[0168] Comparative Example 6 Hollow silica sol 6 obtained in Comparative Example 3 was used instead of hollow silica sol 3 in Example 6, and the rest was the same as in Example 6 to obtain hollow silica-modified isopropanol sol 15 having a solid content of 20.5%.
[0169] Preparation Examples 1 to 12 Antireflective coating compositions and antireflective coating layer preparation examples: Each of the sols prepared in Examples 1 to 6 and Comparative Examples 1 to 6 was diluted with methyl isobutyl ketone (MIBK) to a solid content of 10%. 10 g of the sol with a solid content of 10% was taken, and 1 g of dipentaerythritol hexaacrylate (DPHA), 0.05 g of a photoinitiator (Irgacure-184), and 38.95 g of MIBK were added and mixed uniformly to obtain 50 g of a coating composition with a solid content of 4%.
[0170] The coating composition was applied to a PET film (Gika Toray, Lumirror PY2, thickness 100 microns) using a #3 wire bar (3 microns), dried in an oven at 80°C for 2 minutes, and UV cured (energy 800-1500 mJ / cm2 ) was carried out to obtain a PET product having an anti-reflection film with a thickness of 100 nm. The reflectance, haze value, moist heat resistance, pencil hardness, adhesion, and abrasion resistance of this product were measured, and the results are shown in Table 2.
[0171] Reflectance: Spectral reflectance was measured using a spectrophotometer (UV-3150 manufactured by Shimadzu Corporation) in the wavelength range of 300 to 800 nm at an incident angle of 5 degrees. The average value of the reflectance in the range of 380 to 760 nm was taken as the average reflectance.
[0172] Haze value: The total light transmittance and the haze value were measured using a hazemeter.
[0173] Moisture and heat resistance: The temperature of the thermo-hygrostat chamber was set to 85°C, the humidity to 85%, and the test time to 1000 hours. The moisture and heat resistance was evaluated by measuring the total light transmittance attenuation rate of the PET product, and was classified into the following three levels. ◎: Attenuation rate less than 0.5% 〇: Decay rate 0.5~1.0% ●: Attenuation rate exceeds 1%
[0174] Pencil hardness: The pencil hardness of the resulting coating layer was measured using a pencil scratch tester in accordance with Japan JIS K 5600. The resulting coating layer was rubbed with a pencil at a 45 degree angle from above with a load of 750 g for about 5 cm, and the pencil hardness was expressed as the number of times that no scratches were found in at least 4 out of 5 tries.
[0175] Adhesion: 100 squares were cut into the surface of a PET coating with a knife, cellophane tape was applied over the squares, and the tape was then peeled off to evaluate adhesion by observing the number of squares remaining. The number of remaining squares was classified into the following three levels. ◎: 90~100 ○:80~89 ●: Less than 80
[0176] Abrasion resistance: 500g / cm2, using #0000 steel wool on a 2cm x 2cm whetstone 2 The surface was rubbed back and forth 100 times under a load of 1000 mm, and the state of scratches was visually observed. The evaluation criteria were as follows: Grade 5: No scratches Grade 4: 1 to 10 scratches Grade 3: 10 to 30 scratches Grade 2: More than 30 scratches occurred Grade 1: Scratches and peeling occurred over the entire surface
[0177] [Table 1]
[0178] [Table 2]
[0179] As shown in Table 1, in Examples 1 to 3, the sol viscosity was significantly reduced, the shell surface was denser, the pore size was smaller, and the wall thickness of the hollow particles was thinner, compared to Comparative Examples 1 to 3. The corresponding refractive index and dielectric constant were both reduced, and the particles exhibited excellent low refractive index and dielectric constant.
[0180] As shown in Table 2, when compared with hollow particles that had not been subjected to hydrothermal treatment, the hollow particles that had been subjected to the hydrothermal treatment process showed significant improvements in transmittance, reflectance, moist heat resistance, pencil hardness, adhesion, and abrasion resistance after application to a PET substrate when used in an anti-reflective coating composition.
[0181] Furthermore, when comparing Preparation Examples 1 to 3 with Preparation Examples 7 to 9, the surface-modified hollow particles, when used in an antireflective coating composition, showed improved transmittance, reflectance, haze value, moist heat resistance, pencil hardness, adhesion, and abrasion resistance after application to a PET substrate, compared with hollow particles that had not been surface-modified, and the improvements in haze value and abrasion resistance were particularly notable.
[0182] Therefore, the technical solution of the present invention has excellent anti-reflection properties as well as excellent mechanical properties and weather resistance.
[0183] Other embodiments of the present invention will be readily apparent to those skilled in the art upon consideration of this specification and practice of the disclosed invention. The present invention is intended to cover any variations, uses, or appropriate modifications of the present invention, including those that are within the scope of the general principles of the present invention and that are not disclosed herein but are within the scope of the common technical knowledge or customary means in the art.
Claims
1. A hollow silica sol containing hollow silica particles and a dispersion medium, The hollow silica particles are 29 A resonant peak area Q1 having a chemical shift of −78 to −88 ppm, a resonant peak area Q2 having a chemical shift of −88 to −98 ppm, a resonant peak area Q3 having a chemical shift of −98 to −108 ppm, and a resonant peak area Q4 having a chemical shift of −108 to −117 ppm, which correspond to peaks measured by Si nuclear magnetic resonance spectroscopy, are each determined to satisfy the following conditions: Q1 / (Q1+Q2+Q3+Q4) is 0, Q2 / (Q1+Q2+Q3+Q4) is 0.01 to 0.2, Q3 / (Q1+Q2+Q3+Q4) is 0.01 to 0.6, and Q4 / (Q1+Q2+Q3+Q4) is 0.2 to 0.98, The hollow silica particles have a shell layer having a thickness of 3 to 100 nm, and the pore size distribution of the pores on the shell layer is in the range of 0.5 to 4 nanometers; The hollow silica particles have a pore volume of 0.15 to 1 cm 3 / g, a porosity of 10% to 90%, and a refractive index of 1.10 to 1.267; The dispersion medium is water, an organic solvent, or a combination of both; The hollow silica sol has a viscosity of 5 to 200 mPa·sec at 25° C. and a solid content of 20%.
2. The hollow silica sol according to claim 1, wherein the hollow silica particles have a relative dielectric constant of 1.6 to 2.
2.
3. 2. The hollow silica sol according to claim 1, wherein the hollow silica particles have a particle diameter of 15 to 1000 nm as measured by a dynamic light scattering method and a polydispersity index of 0.05 to 0.
3.
4. an intermediate product producing step of mixing a silicon source, a first solvent, a first catalyst and an active compound, reacting them at a temperature in the range of 0°C to 150°C, and then removing those having a boiling point of less than 300°C to obtain a liquid silicone intermediate product P1; a hollow silica production step of dispersing the silicone intermediate product P1 in a second solvent, adding a second catalyst, and reacting at a temperature in the range of 0° C. to 95° C. to obtain a hollow silica sol; a hydrothermal treatment step in which hydrothermal treatment is performed in the range of 30°C to 300°C; The method for preparing hollow silica sol according to claim 1, comprising:
5. The method for preparing hollow silica sol according to claim 4, wherein in the intermediate product generating step, the silicon source is one or more selected from silane monomers represented by the following formula I, or a polyalkoxysiloxane oligomer whose empirical formula is represented by the following formula II. R 1 4-n Si(OR 2 ) n Formula I wherein n is 1, 2, 3 or 4; R 1 is an alkyl group, a vinylalkyl group, a vinyl group, an epoxyalkyl group, a phenyl group, a styrylalkyl group, a methacryloxyalkyl group, an acryloxyalkyl group, an aminoalkyl group, a urethane group, a chloroalkyl group, a mercaptoalkyl group, an isocyanatoalkyl group, or a hydroxyalkyl group; R 1 If there are multiple R 1 may be the same or different, R 2 is an alkyl group having 1 to 6 carbon atoms; R 2 If there are multiple R 2 may be the same or different.) SiO m (OR 3 ) 4-2m Formula II (Wherein, 0<m<2, m is an integer or a non-integer; R 3 is an alkyl group having 1 to 6 carbon atoms; R 3 If there are multiple R 3 may be the same or different.)
6. 6. The method for preparing hollow silica sol according to claim 4 or 5, wherein in the intermediate product generation step, the first solvent is water or an organic solvent containing water, and the weight ratio of water to the silicon source is 0.001:1 or more and less than 0.5:
1.
7. The method for preparing hollow silica sol according to claim 4, wherein in the intermediate product generating step, the first catalyst is an acid or a base, and the weight ratio of the first catalyst to the silicon source is (0.001 to 0.5):
1.
8. In the intermediate product production step, the active compound contains at least one OH group and has a molecular weight of more than 150, and the HLB value of the active compound calculated by the following formula III is more than 5; The method for preparing hollow silica sol according to claim 4, wherein the weight ratio of said active compound to said silicon source is (0.05-0.5):1, and said active compound is one kind or a mixture of two or more kinds. HLB=20×M h / M Type III (In the formula, M h is the molecular weight of the hydrophilic portion of the active compound, and M is the molecular weight of the active compound.
9. In the hollow silica generating step, the second solvent is water, a mixture of water and a hydrophilic organic solvent, or a mixture of water and a hydrophobic organic solvent, the second catalyst is an acid or a base; the weight percentage of said silicone intermediate product P1 relative to said second solvent is 1 to 60%; The method for preparing hollow silica sol according to claim 4, wherein the weight ratio of the second catalyst to the silicone intermediate product P1 is (0.05-2):
1.
10. The method further comprises a solvent replacement step of replacing the solvent of the hollow silica sol, The method for preparing a hollow silica sol according to claim 4, wherein in the solvent replacement step, all or a part of the solvent in the hollow silica sol is replaced by centrifugation, heating azeotropy or ultrafiltration treatment.
11. The method further includes a surface modification step of adding one or more members selected from the group consisting of a silane represented by the following formula IV and / or a partial hydrolyzate thereof, hexamethyldisiloxane, and hexamethyldisilazane to the hollow silica sol to modify the surfaces of the hollow silica particles, The method for preparing a hollow silica sol according to claim 4 , wherein the surface modification step is carried out after the hollow silica production step and / or after the hydrothermal treatment step. R 4 p -Si-X 4-p Formula IV (wherein p is 0, 1, 2 or 3; R 4 is selected from an alkyl group, a vinyl alkyl group, an epoxy alkyl group, a styryl alkyl group, a methacryloxy alkyl group, an acryloxy alkyl group, an amino alkyl group, a urethane group, a chloro alkyl group, a mercapto alkyl group, an isocyanato alkyl group, or a hydroxy alkyl group; R 4 If there are multiple R 4 may be the same or different, R 4 may be substituted with fluorine atoms, X is selected from an alkoxy group having 1 to 6 carbon atoms, a halogen, or hydrogen, and when there are multiple X's, each X may be the same or different.
12. The method further includes a surface modification step of adding one or more members selected from the group consisting of a silane represented by the following formula IV and / or a partial hydrolyzate thereof, hexamethyldisiloxane, and hexamethyldisilazane to the hollow silica sol to modify the surfaces of the hollow silica particles, The method for preparing a hollow silica sol according to claim 10, wherein the surface modification step is carried out after the hollow silica production step, and / or after the hydrothermal treatment step, and / or after the solvent replacement step. R 4 p -Si-X 4-p Formula IV (wherein p is 0, 1, 2 or 3; R 4 is selected from an alkyl group, a vinyl alkyl group, an epoxy alkyl group, a styryl alkyl group, a methacryloxy alkyl group, an acryloxy alkyl group, an amino alkyl group, a urethane group, a chloro alkyl group, a mercapto alkyl group, an isocyanato alkyl group, or a hydroxy alkyl group; R 4 If there are multiple R 4 may be the same or different, R 4 may be substituted with fluorine atoms, X is selected from an alkoxy group having 1 to 6 carbon atoms, a halogen, or hydrogen, and when there are multiple X's, each X may be the same or different.
13. The method for preparing a hollow silica sol according to claim 12 , wherein the hydrothermal treatment step and / or the solvent replacement step are carried out again after the surface modification step.
14. A coating composition comprising a hollow silica sol and an adhesive, wherein the hollow silica sol is the sol according to claim 1.
15. A product having a coating layer on a surface of a substrate, the coating layer being one layer or two or more layers, at least one of the coating layers being formed by curing the coating composition according to claim 14.
Citation Information
Patent Citations
Nanometer material with controllable particle sizes and silicon dioxide hollow spheres and method for preparing nanometer material
CN106044788A
Preparation method of anti-reflective coating material composition containing silica hollow particles
CN110128855A
Ultralow dielectric constant hollow silicon dioxide material for 5G high-frequency and preparation method thereof
CN111232993A
Water-base silica dispersion
JP2004107204A
Silica and method of manufacturing the same
JP2005022895A